Quantitative agreement between [15O]H2O PET and model free QUASAR MRI‐derived cerebral blood flow and arterial blood volume. (15th February 2016) - Heijtel, D.F.R.; Petersen, E.T.; Mutsaerts, H.J.M.M.; Bakker, E.; Schober, P.; Stevens, M.F.; van Berckel, B.N.M; Majoie, C.B.L.M.; Booij, J.; van Osch, M.J.P.; van Bavel, E.T.; Boellaard, R.; et al.
Abstract : The purpose of this study was to assess whether there was an agreement between quantitative cerebral blood flow (CBF) and arterial cerebral blood volume (CBVA) measurements by [ 15 O]H2 O positron emission tomography (PET) and model‐free QUASAR MRI. Twelve healthy subjects were scanned within a week in separate MRI and PET imaging sessions, after which quantitative and qualitative agreement between both modalities was assessed for gray matter, white matter and whole brain region of interests (ROI). The correlation between CBF measurements obtained with both modalities was moderate to high ( r 2 : 0.28–0.60, P  < 0.05), although QUASAR significantly underestimated CBF by 30% ( P  < 0.001). CBVA was moderately correlated ( r 2 : 0.28–0.43, P  < 0.05), with QUASAR yielding values that were only 27% of the [ 15 O]H2 O‐derived values ( P  < 0.001). Group‐wise voxel statistics identified minor areas with significant contrast differences between [ 15 O]H2 O PET and QUASAR MRI, indicating similar qualitative CBVA and CBF information by both modalities. In conclusion, the results of this study demonstrate that QUASAR MRI and [ 15 O]H2 O PET provide similar CBF and CBVA information, but with systematic quantitative discrepancies. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This study assessed the cerebral blood flow (CBF) and arterial blood volume (CBVA ) agreement between [ 15 O]H2 O PET and model‐free QUASAR MRI, in a group of 12 healthy volunteers. Qualitatively, model‐free QUASAR MRI and [ 15 O]H2 O PET provide similar CBF and CBVA information. However quantitatively, significant systemic discrepancies were observed between the modalities.